2014
DOI: 10.1080/03088839.2014.926032
|View full text |Cite
|
Sign up to set email alerts
|

Common patterns in aggregated accident analysis charts from human fatigue-related groundings and collisions at sea

Abstract: Research has shown that there are potentially disastrous outcomes of human fatigue at sea. The conditions in which the seafarers have to operate are becoming more and more demanding. The study in this article attempts to aggregate accident charts derived from in-depth studies of human fatigue-related accidents to determine common patterns of interlinked fatigue factors. The accidents are analyzed by means of the Cognitive Reliability and Error Analysis Method (CREAM), which in the article has been modified for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…The study shows that there are positive associations between key safety climate components, such as local management, working practices and reporting practices, and overall safety evaluation among the crew (Oltedal and Wadsworth 2010). Also, Akhtar and Utne (2015) recently analysed groundings and collisions related to human fatigue. The general picture found for both types of accidents was that many of the factors related to fatigue (e.g.…”
Section: Safety Climatementioning
confidence: 89%
“…The study shows that there are positive associations between key safety climate components, such as local management, working practices and reporting practices, and overall safety evaluation among the crew (Oltedal and Wadsworth 2010). Also, Akhtar and Utne (2015) recently analysed groundings and collisions related to human fatigue. The general picture found for both types of accidents was that many of the factors related to fatigue (e.g.…”
Section: Safety Climatementioning
confidence: 89%
“…In more recent research, Celik and Cebi (2009) applied a Human Factors Analysis and Classification System (HFACS) initially from the aviation transportation (Wiegmann and Shappell, 2017) Celik (2015) adopted CREAM to assess human reliability under a cargo loading process. Akhtar and Utne (2015) investigated the common patterns of interlinked fatigue factors. It was illustrated that "inattention", "inadequate procedures", "observation missed", and "communication failure" were related to fatigue factors that influence the human cognitive processes in accidents.…”
Section: Human Errors In Maritime Operationsmentioning
confidence: 99%
“…Talley, Jin, and Kite-Powell (2005; found that the majority of accidents with crew or passenger injuries are due to human factors. Harati-Mokhtari et al (2007) asked attention for technological innovations and the importance of man-machine collaboration; see also Akhtar and Utne (2015) and Mindykowski (2017). Hetherington, Flin, and Mearns (2006) reviewed various human factors that affect safety at sea, including fatigue, automation, communication, team work, health and stress.…”
Section: Human Factor Aspects In Shipping Safetymentioning
confidence: 99%
“…Oltedal and Wadsworth (2010) investigated the relation between safety culture, shipboard safety, and organizational factors. Akhtar and Utne (2015) considered fatigue-related groundings and collisions, and Besikci, Tavacioglu, and Arslan (2016) analysed stress and fatigue of seafarers. Progoulaki and Theotokas (2016) discussed managing crews of mixed nationalities.…”
Section: Human Factor Aspects In Shipping Safetymentioning
confidence: 99%